Dielectric ceramic composition and ceramic capacitor using the same

By using new dielectric ceramic compositions and suitable dopants, a multi-layer ceramic capacitor with excellent thermal stability and low leakage current is solved, and the problem of unstable capacitance characteristics in the prior art under high temperature environments is achieved, capacitance stability and high insulation performance over a wide temperature range are achieved.

CN116615399BActive Publication Date: 2025-03-21KEMET ELECTRONICS CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202280008247.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-01-28
Filing Date
2022-01-27
Publication Date
2025-03-21
Estimated Expiration
2042-01-27

AI Technical Summary

Technical Problem

It is difficult for existing multi-layer ceramic capacitors to maintain stable capacitance characteristics under high temperature environments (175°C-200°C), and the dielectric materials used are prone to introduce high leakage currents.

Method used

Using a new dielectric ceramic composition [(Na1-xKx)sA1-s]m[(Nb1-yTay)uB1vB2w)]O3, a multi-layer ceramic capacitor with excellent thermal stability and low leakage current is formed by reasonably selecting the mole fraction of alkaline earth elements, transition metal elements and rare earth elements, combined with appropriate dopants and sintering processes.

Benefits of technology

The stability of the capacitance temperature coefficient within ±25% in the temperature range of -55°C to 200°C and the dielectric constant reaches at least 100 at 25°C, preferably between 900 and 2000, significantly reducing the leakage current and improving the insulation stability and life reliability of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004288760310000011
    Figure HDA0004288760310000011
Patent Text Reader

Abstract

The present invention discloses a dielectric ceramic formulation product, which can obtain a multilayer ceramic capacitor by alternately stacking ceramic dielectric layers and base metal internal electrodes. The dielectric ceramic composition includes the main components: [(Na 1‑x K x ) s A 1‑s ] m [(Nb 1‑y Ta y ) u B1 v B2 w )]O3 wherein: A is at least one selected from the alkaline earth element group of Mg, Ca, Sr and Ba; B1 is at least one selected from Ti, Zr, Hf and Sn; B2 is at least one selected from transition metal elements; and wherein: x, y, s, u, v and w are the mole fractions of each element, and m is [(Na 1‑ x K x ) s A 1‑s ] and [(Nb 1‑y Ta y ) u B1 v B2 w )] in the following molar ratios: 0.93≤m≤1.07; 0.7≤s≤1.0; 0≤x≤0.05; 0≤y≤0.65; 0.7≤u≤1.0; 0≤v≤0.3; 0.001≤w≤0.100.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to pending U.S. provisional application No. 63 / 142,752, filed on January 28, 2021, which is incorporated herein by reference. Technical Field

[0003] The present invention relates to a dielectric ceramic formulation product and a multilayer ceramic capacitor using the same. The dielectric ceramic formulation product can be co-fired with an internal electrode comprising a base metal under low oxygen partial pressure, and the multilayer ceramic capacitor manufactured therefrom can be used for high temperature applications. Background Art

[0004] In the past two decades, with the booming development of the information industry and the electronics industry, the multilayer ceramic capacitor manufacturing industry has flourished due to the increasing demand for electrical energy storage components in numerous applications (such as portable electronic devices, personal computers, cellular phones, televisions, etc.). In these cases, BaTiO3 is widely used as a basic ceramic dielectric material due to its high dielectric constant, low dielectric loss, and stable capacitance change in the temperature range of -55℃ to 125℃. However, BaTiO3 is a well-known ferroelectric material that undergoes a ferroelectric-paraelectric phase transition around 125℃, resulting in a significant decrease in the dielectric constant and a sharp drop in the temperature coefficient of capacitance. Nowadays, with the emergence of new electronic applications in extreme environments (such as engine control units, downhole drilling, pulse power electronics, etc.), it is necessary to maintain stable capacitance within the maximum operating temperature window of 175℃-200℃ or even higher. Although a large number of research activities have been carried out to stabilize the temperature-capacitance characteristics of BaTiO3-based capacitors through a wide range of doping modification packaging, the extended operating temperature is still limited to around 150℃. Therefore, the development of new dielectric materials that can be used in harsh environments at 175°C-200°C or above has attracted considerable attention. Recently, alkaline niobate-based ceramics (such as NaNbO3) have been found to be viable candidates for the development of high-temperature capacitors through appropriate doping selection. Doping with alkaline earth zirconates (such as CaZrO3 and SrZrO3) or alkaline earth hafnates (such as CaHfO3 and SrHfO3) has also been considered.

[0005] Detailed firing studies and defect chemistry studies reported in the literature have shown that alkaline niobate-based ceramics can be co-fired with base metals (such as Cu and Ni) at low oxygen partial pressures due to carefully designed chemical thermodynamics that mitigate the volatility of alkaline elements. U.S. Patent No. 9,564,271 and WO 2018 / 062084A1 (both of which are incorporated herein by reference) respectively demonstrate that (K,Na)NbO3-based ceramics and NaNbO3-based ceramics are compatible with co-firing with Ni internal electrodes in a reducing atmosphere. However, the dielectric ceramic compositions disclosed in both documents include Li. As a light element, Li is known to be easily mobile in electronic ceramic materials and may introduce high leakage currents, especially in harsh environments (e.g., at high voltages and / or high temperatures), or in humid environments. Obviously, this leakage current is detrimental to dielectric capacitors in terms of insulation stability and lifetime reliability.

[0006] Despite significant efforts, new formulations are still needed to meet the demands of modern electronics. Summary of the invention

[0007] The present invention relates to improved ceramics, wherein the ceramics exhibit excellent thermal stability. The present invention also relates to improved capacitors comprising the improved ceramics.

[0008] As will be appreciated, these and other embodiments provide a dielectric ceramic composition comprising:

[0009] The main components are defined as:

[0010] [(Na 1-x K x ) s A 1-s ] m [(Nb 1-y Ta y ) u B1 v B2 w )]O3

[0011] in:

[0012] A is at least one element selected from the alkaline earth element group of Mg, Ca, Sr and Ba;

[0013] B1 is at least one element selected from Ti, Zr, Hf and Sn;

[0014] B2 is at least one element selected from the transition metal element group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn;

[0015] And among them:

[0016] x, y, s, u, v and w are the mole fractions of the elements; and

[0017] m is [(Na 1-x K x ) s A 1-s ] and [(Nb 1-y Ta y ) u B1 v B2 w )] molar ratio;

[0018] in

[0019] 0.93≤m≤1.07;

[0020] 0.7≤s≤1.0;

[0021] 0≤x≤0.05;0≤y≤0.65;

[0022] 0.7≤u≤1.0; 0≤v≤0.3; 0.001≤w≤0.100;

[0023] A first subcomponent comprising at least one rare earth selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu; and

[0024] The second component includes glass material.

[0025] Another embodiment provides a multilayer ceramic capacitor, comprising:

[0026] A plurality of dielectric ceramic layers, wherein each layer comprises a dielectric composition defined by:

[0027] The main components are defined as:

[0028] [(Na 1-x K x ) s A 1-s ] m [(Nb 1-y Ta y ) u B1 v B2 w )]O3

[0029] in:

[0030] A is at least one element selected from the alkaline earth element group of Mg, Ca, Sr and Ba;

[0031] B1 is at least one element selected from the group consisting of Ti, Zr, Hf and Sn;

[0032] B2 is at least one element selected from the transition metal element group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn;

[0033] And among them:

[0034] x, y, s, u, v and w are the mole fractions of the elements; and

[0035] m is [(Na 1-x K x ) s A 1-s ] and [(Nb 1-y Ta y ) u B1 v B2 w )] molar ratio;

[0036] in:

[0037] 0.93≤m≤1.07;

[0038] 0.7≤s≤1.0;

[0039] 0≤x≤0.05;0≤y≤0.65;

[0040] 0.7≤u≤1.0; 0≤v≤0.3; 0.001≤w≤0.100;

[0041] A first subcomponent comprising at least one rare earth selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu; and

[0042] The second auxiliary component includes glass material;

[0043] a plurality of internal electrodes comprising a base metal such as Ni, Cu or an alloy thereof; and

[0044] A pair of external electrodes are formed at each end of the capacitor element body.

[0045] Another embodiment provides a method of forming a multilayer ceramic capacitor, comprising:

[0046] forming a dielectric ceramic precursor;

[0047] interleaving layers of the dielectric ceramic precursor with metal layers to form a stack;

[0048] Compressing the stack and sintering the dielectric precursor to form a dielectric ceramic layer having a composition defined by:

[0049] The main components are defined as:

[0050] [(Na 1-x K x ) s A 1-s ] m [(Nb 1-y Ta y ) u B1 v B2 w )]O3

[0051] in:

[0052] A is at least one element selected from the alkaline earth element group of Mg, Ca, Sr and Ba;

[0053] B1 is at least one element selected from Ti, Zr, Hf and Sn;

[0054] B2 is at least one element selected from the transition metal element group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn;

[0055] And among them:

[0056] x, y, s, u, v and w are the mole fractions of the elements; and

[0057] m is [(Na 1-x K x ) s A 1-s ] and [(Nb 1-y Ta y ) u B1 v B2 w )] molar ratio;

[0058] in

[0059] 0.93≤m≤1.07;

[0060] 0.7≤s≤1.0;

[0061] 0≤x≤0.05;

[0062] 0≤y≤0.65;

[0063] 0.7≤u≤1.0;

[0064] 0≤v≤0.3;

[0065] 0.001≤w≤0.100;

[0066] A first subcomponent comprising at least one rare earth selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu; and

[0067] The second component includes glass material. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 FIG. 1 is a schematic cross-sectional view of a multilayer ceramic capacitor using the dielectric ceramic composition according to the present invention. DETAILED DESCRIPTION

[0069] The present invention provides a dielectric ceramic composition that can achieve good temperature-capacitance characteristics from low temperature to high temperature. Specifically, the capacitor made from the disclosed dielectric ceramic composition can have a capacitance temperature coefficient within ±25% in the temperature range of -55°C to 200°C relative to the capacitance at 25°C. The dielectric constant of the dielectric ceramic of the present invention at 25°C is at least 100, preferably at least 900 to no more than 2000.

[0070] The present invention also provides a dielectric ceramic composition that is compatible with co-fired internal electrodes using inexpensive base metals (eg, Ni, etc.) in a reducing atmosphere.

[0071] Therefore, the present invention provides a multilayer ceramic capacitor device, which is formed by a plurality of laminated ceramic layers and a plurality of internal electrode layers in a pattern in which the ceramic layers and the internal electrode layers are alternately stacked. The ceramic layers are made of the dielectric composition of the present invention, and the internal electrode layers are made of a conductive paste mainly containing base metals (such as Ni, etc.). After co-firing under low oxygen partial pressure, the capacitance temperature coefficient of the obtained multilayer ceramic capacitor in the temperature range of -55°C to 200°C can be within ±25%.

[0072] The above objects can be achieved in a multilayer ceramic capacitor device having a dielectric ceramic composition including:

[0073] [(Na 1-x K x ) s A 1-s ] m [(Nb 1-y Ta y ) u B1 v B2 w )]O3

[0074] in:

[0075] A is at least one selected from the group consisting of alkaline earth elements: Mg, Ca, Sr and Ba;

[0076] B1 is at least one selected from Ti, Zr, Hf and Sn;

[0077] B2 is at least one selected from transition metal elements;

[0078] And among them:

[0079] x, y, s, u, v and w are the mole fractions of each element, and m is [(Na 1-x K x ) s A 1-s ] and [(Nb 1-y Ta y ) u B1 v B2 w )] in the following ranges:

[0080] 0.93≤m≤1.07;

[0081] 0.7≤s≤1.0;

[0082] 0≤x≤0.05; 0≤y≤0.65; and

[0083] 0.7≤u≤1.0; 0.0≤v≤0.3; 0.001≤w≤0.100.

[0084] In addition to the main ingredients, it also includes secondary ingredients.

[0085] The first subcomponent includes at least one element selected from rare earth compounds, which does not exceed 10 mol% relative to the main component; and a second subcomponent composed of a compound with a low melting temperature (also called glass frit) to assist the ceramic sintering process, the second subcomponent does not contain lithium, and is preferably selected from at least one compound selected from fluorides, silicates, borides and oxides. The content of the glass frit is 0.01 mol% to 15.00 mol% relative to the main component.

[0086] In order to obtain the disclosed dielectric ceramic composition, (1) a precursor is first prepared upon calcination; a precursor is defined herein as an intermediate compound or group of compounds produced from certain ceramic raw material powders, wherein the precursor may contain all or part of the constituent elements of the final composition, but the final form of the material is not obtained until the precursor is further mixed with other reactants and treated under certain thermal conditions to obtain the desired chemical properties; (2) the obtained mixture of the precursor and other dopants (such as transition metal compounds, rare earth compounds and glass frits) is then further prepared in the form of a slurry with the assistance of various organic mixtures before sintering; and (3) finally, the composition including the resulting slurry mixture forms the dielectric ceramic material disclosed in the present invention during sintering. Table 1 lists an example. The precursor mainly comprises NaNbO3-SrZrO3 ceramics, which are prepared by calcining pre-reacted oxides and carbonates (such as Na2CO3, SrCO3, Nb2O5 and ZrO2). The inorganic dopants used to form the slurry before sintering are MnCO3, CeO2 and SiO2.

[0087] Table 1

[0088] Compounds used to form precursors <![CDATA[Na2CO3、SrCO3、Nb2O5、ZrO2]]> Dopant <![CDATA[MnCO3、CeO2、SiO2]]>

[0089] The dielectric ceramic material can also be obtained by another route starting from more than one precursor, as shown in Table 2, using the same starting materials as Table 1. In this case, two precursors are prepared separately by calcination, Precursor 1 mainly containing NaNbO3 and Precursor 2 mainly containing SrZrO3. Then, a slurry is formed from a mixture of NaNbO3, SrZrO3, MnCO3, CeO2 and SiO2 together with an organic mixture. After sintering, the formulation of Table 2 will produce a dielectric material composition that is substantially the same as the dielectric material composition prepared by the formulation of Table 1.

[0090] Table 2

[0091] Compounds used to form precursor 1 <![CDATA[Na2CO3、Nb2O5]]> Compounds used to form precursor 2 <![CDATA[SrCO3、ZrO2 <!-- 4 -->]]> Dopant <![CDATA[MnCO3、CeO2、SiO2]]>

[0092] The following description shows the above-mentioned features and other features of the present invention with more complete examples, but is not limited thereto. However, these examples are only indicative of several of the various ways in which the principles of the present invention can be employed, and are not intended to limit the scope of the present invention.

[0093] The dielectric ceramic composition of the present invention comprises a main component and a subsidiary component, wherein the main component is represented by the following formula:

[0094] [(Na 1-x K x ) s A 1-s ] m [(Nb 1-y Tay ) u B1 v B2 w )]O3 (1)

[0095] in:

[0096] A is at least one selected from the group consisting of alkaline earth elements of Mg, Ca, Sr and Ba; preferably, A is Ba, Sr and / or Ca.

[0097] B1 is at least one selected from Ti, Zr, Hf and Sn; preferably B1 is Zr and / or Hf;

[0098] B2 is a transition metal element, preferably selected from one of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, Zn and combinations thereof; preferably B2 is at least one of V, W, Mo, Cr and Mn.

[0099] In formula (1), x, y, s, u, v and w are the mole fractions of the respective elements, and m is [(Na 1-x K x ) s A 1-s ] and [(Nb 1- y Ta y ) u B1 v B2 w )] in the following ranges:

[0100] 0.93≤m≤1.07;

[0101] 0.7≤s≤1.0;

[0102] 0≤x≤0.05;0≤y≤0.65;

[0103] 0.7≤u≤1.0; 0≤v≤0.3; 0.001≤w≤0.100;

[0104] The first auxiliary component includes at least one rare earth element, preferably selected from Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu. The amount of the rare earth element added is not more than 10 mol% relative to the main component. 3 / 2 ScO 3 / 2 、LaO 3 / 2 、CeO2、PrO 11 / 6 、NdO 3 / 2 、SmO 3 / 2 ,EuO 3 / 2 , GdO 3 / 2 , TbO 7 / 4, DyO 3 / 2 、HoO 3 / 2 , ErO 3 / 2 、TmO 3 / 2 , YbO 3 / 2 and LuO 3 / 2 Calculate the mole fraction value.

[0105] The second auxiliary component includes a compound with a low melting temperature (called glass frit) to assist the ceramic sintering process. The glass frit composition is not limited to any form, and preferably can be selected from fluorides (such as NaF, KF, MgF2), silicates (such as Si, SiO2, (Ba x Sr y Ca 1-x-y )SiO3 (0≤x, y≤1)), at least one of a boride (such as B2O3) and an oxide (such as Na2O, MoO3, V2O5, etc.). The glass frit content is 0.01 mol% to 15.00 mol% relative to the main component. The glass frit does not contain Li as a main component, which is defined as less than 0.10 mol% lithium, preferably less than 0.05 mol% lithium, more preferably less than 0.01 mol% lithium, and even more preferably below the detectable limit of lithium in view of the Li impurity that cannot be actually eliminated.

[0106] In order to obtain the public Figure 1 The dielectric ceramic composition in the ceramic layer 2 in the multilayer ceramic capacitor 1 shown is prepared with K2CO3, Na2CO3, BaCO3, SrCO3, CaCO3, Ta2O5, Nb2O5, TiO2, ZrO2, HfO2, transition metal compounds, rare earth compounds and glass frit as starting ceramic raw materials. The proportions of these compounds in the raw materials are predetermined so that after sintering, the dielectric ceramic composition disclosed in the present invention can be obtained. In addition, not only oxides and carbonates but also hydroxides can be used as raw material compounds of the various constituent elements contained in the disclosed dielectric formulation product. Specifically, the raw materials are not limited to any form. For example, Mn can be added in the form of MnO, MnO2, MnCO3, etc.; this applies to all other raw materials. The main constituent raw materials are weighed to meet the disclosed composition formulation product, and then wet mixed with a suitable solvent (e.g., water, ethanol, isopropanol, toluene, ethyl acetate, propyl acetate, butyl acetate, mineral solvent or other suitable hydrocarbon liquid or a mixture thereof) through a ball mill with yttrium-stabilized zirconium media. After drying and calcination, a ceramic material is thus obtained before sintering.

[0107] Water and / or suitable organic additives (such as binders, dispersants, solvents, plasticizers, etc.) are added and the calcined powder described herein is further wet-milled to form a ceramic slip. There is no particular restriction on the selection of organic additives or the selection of organic content used herein.

[0108] In order to obtain the ceramic slurry described in this article and the ceramic composition disclosed below, the preparation steps are not limited to the above process, and the precursor material can be first prepared by calcination, and then mixed with a precursor or dopant containing other constituent elements of the desired composition to form a ceramic slurry with a suitable organic additive before sintering.

[0109] Embodiment 1 to Embodiment 4 illustrate the present invention, but they do not limit the scope of the present invention thereto. Modifications that are obvious to those skilled in the art are included in the scope of the present invention.

[0110] Example 1

[0111] K2CO3, Na2CO3, BaCO3, SrCO3, CaCO3, Ta2O5, Nb2O5, TiO2 and ZrO2 are mixed as starting ceramic raw materials and calcined at 750°C to 1300°C to prepare a precursor, wherein the starting ceramic materials include:

[0112] 0.1 mol% to 2.0 mol% K from K2CO3;

[0113] 90.0 mol % to 95.5 mol % Na from Na2CO3;

[0114] 0.1 mol% to 2.7 mol% Ba from BaCO3;

[0115] 0.1 mol% to 5.3 mol% Sr from SrCO3;

[0116] 0.1 mol% to 6.6 mol% Ca from CaCO3;

[0117] 0.1 mol% to 5.5 mol% Ta from Ta2O5;

[0118] 90.0 mol% to 95.5 mol% Nb from Nb2O5;

[0119] 0.05 mol % to 1.20 mol % Ti from TiO2;

[0120] 0.1 mol% to 6.6 mol% Zr from ZrO2;

[0121] A mixture of transition metal oxides, rare earth oxides and glass frits including the following is then added as a dopant along with suitable organic additives to form a ceramic slip:

[0122] 0.1 mol% to 2.4 mol% Mn from MnO2;

[0123] 0.2 mol% to 4.8 mol% from Pr6O 11 Pr;

[0124] 0.01 mol% to 3.30 mol% of glass frit from SiO2.

[0125] Example 2

[0126] K2CO3, Na2CO3, BaCO3, SrCO3, CaCO3, Ta2O5, Nb2O5, ZrO2, HfO2 and transition metal oxides (such as MnO2 and MoO3) are mixed as starting ceramic raw materials to prepare a precursor after calcination at 750°C to 1300°C, wherein the starting ceramic material includes:

[0127] 0.1 mol% to 2.0 mol% K from K2CO3;

[0128] 90.0 mol % to 95.5 mol % Na from Na2CO3;

[0129] 0.1 mol% to 1.7 mol% Ba from BaCO3;

[0130] 0.1 mol% to 3.3 mol% Sr from SrCO3;

[0131] 0.1 mol% to 6.6 mol% Ca from CaCO3;

[0132] 0.1 mol% to 5.5 mol% Ta from Ta2O5;

[0133] 90.0 mol% to 95.5 mol% Nb from Nb2O5;

[0134] 0.1 mol% to 6.6 mol% Zr from ZrO2;

[0135] 0.05 mol % to 1.20 mol % Hf from HfO2;

[0136] 0.1 mol% to 2.4 mol% Mn from MnO2;

[0137] 0.01 mol% to 0.80 mol% Mo from MoO3;

[0138] A mixture of rare earth oxides and glass frits including the following is then added as a dopant along with suitable organic additives to form a ceramic slip:

[0139] 0.6 mol% to 5 mol% Y from Y2O3;

[0140] 0.01 mol% to 3.30 mol% of glass frit from CaSiO3.

[0141] Example 3

[0142] Na2CO3, SrCO3, CaCO3, Ta2O5, Nb2O5, ZrO2, HfO2 and rare earth oxide (such as Y2O3) are mixed as starting ceramic raw materials, and calcined at 750°C to 1300°C to prepare a precursor, wherein the starting ceramic material includes:

[0143] 87.0 mol% to 92.5 mol% Na from Na2CO3;

[0144] 0.1 mol% to 5.3 mol% Sr from SrCO3;

[0145] 0.1 mol% to 6.6 mol% Ca from CaCO3;

[0146] 0.1 mol% to 5.5 mol% Ta from Ta2O5;

[0147] 90.0 mol% to 95.5 mol% Nb from Nb2O5;

[0148] 0.1 mol% to 6.6 mol% Zr from ZrO2;

[0149] 0.05 mol % to 1.20 mol % Hf from HfO2;

[0150] 0.2 mol% to 3.7 mol% from Pr6O 11 Pr;

[0151] A mixture of transition metal oxides, rare earth oxides and glass frits including the following is then added as a dopant along with suitable organic additives to form a ceramic slip:

[0152] 0.1 mol% to 2.7 mol% Mn from MnO2;

[0153] 0.01 mol% to 3.30 mol% of the glass frit from NaF.

[0154] Example 4

[0155] Na2CO3, SrCO3, CaCO3, Ta2O5, Nb2O5, ZrO2, transition metal oxides (such as MnO2) and rare earth oxides (such as La2O3) are mixed as starting ceramic raw materials, and calcined at 750° C. to 1300° C. to prepare a precursor, wherein the starting ceramic materials include:

[0156] 87.0 mol% to 92.5 mol% Na from Na2CO3;

[0157] 0.1 mol% to 5.3 mol% Sr from SrCO3;

[0158] 0.1 mol% to 6.6 mol% Ca from CaCO3;

[0159] 0.1 mol% to 5.5 mol% Ta from Ta2O5;

[0160] 87.0 mol% to 92.5 mol% Nb from Nb2O5;

[0161] 0.1 mol% to 6.6 mol% Zr from ZrO2;

[0162] 0.1 mol% to 2.4 mol% Mn from MnO2;

[0163] 0.2 mol% to 4.8 mol% La from La2O3;

[0164] Glass frits including the following are then added as dopants along with suitable organic additives to form a ceramic slip:

[0165] 0.01 mol% to 5.90 mol% NaF.

[0166] In addition, dopants (such as transition metal compounds, rare earth compounds and glass materials) can also be added in two separate steps to obtain the desired dielectric composition disclosed in the present invention. This means that a partial amount of transition metal compounds, rare earth compounds and / or glass materials are first added to the raw materials, and a precursor is prepared after calcination at 750°C to 1300°C, which is defined as step 1; then another amount of transition metal compounds, rare earth compounds and / or glass materials are further added to the precursor together with suitable organic additives to form a ceramic slurry, which is defined as step 2. The transition metal compound added in step 1 and step 2 may be the same compound containing the same target transition metal element, or may be different compounds containing different target transition metal elements. If rare earth compounds and glass materials are added in step 1 and step 2, respectively, this also applies to them. The total amount of transition metal elements, rare earth elements and glass materials added in step 1 and step 2 meets the numerical range specified in the present invention.

[0167] Examples 5 to 9 illustrate the present invention, but they do not limit the scope of the present invention. Modifications that are obvious to those skilled in the art are included in the scope of the present invention.

[0168] Example 5

[0169] Na2CO3, BaCO3, SrCO3, CaCO3, Ta2O5, Nb2O5, ZrO2, HfO2 and transition metal oxides (such as MoO3) are mixed as starting ceramic raw materials and calcined at 750°C to 1300°C to prepare a precursor, wherein the starting ceramic materials include:

[0170] 87.0 mol% to 92.5 mol% Na from Na2CO3;

[0171] 0.1 mol% to 2.7 mol% Ba from BaCO3;

[0172] 0.1 mol% to 5.3 mol% Sr from SrCO3;

[0173] 0.1 mol% to 6.6 mol% Ca from CaCO3;

[0174] 0.1 mol% to 5.5 mol% Ta from Ta2O5;

[0175] 87.0 mol% to 92.5 mol% Nb from Nb2O5;

[0176] 0.1 mol% to 6.6 mol% Zr from ZrO2;

[0177] 0.05 mol % to 1.20 mol % Hf from HfO2;

[0178] 0.01 mol% to 0.80 mol% Mo from MoO3;

[0179] A mixture of transition metal oxides, rare earth oxides and glass frits including the following is then added as a dopant along with suitable organic additives to form a ceramic slip:

[0180] 0.1 mol% to 2.4 mol% Mn from MnO2;

[0181] 0.6 mol% to 5.0 mol% Y from Y2O3;

[0182] 0.01 mol% to 5.90 mol% of the glass frit from NaF.

[0183] Example 6

[0184] Na2CO3, BaCO3, SrCO3, CaCO3, Ta2O5, Nb2O5, TiO2, ZrO2, HfO2 and rare earth oxide (such as Y2O3) are mixed as starting ceramic raw materials, and calcined at 750°C to 1300°C to prepare a precursor, wherein the starting ceramic material includes:

[0185] 90.0 mol % to 95.5 mol % Na from Na2CO3;

[0186] 0.1 mol% to 1.7 mol% Ba from BaCO3;

[0187] 0.1 mol% to 3.3 mol% Sr from SrCO3;

[0188] 0.1 mol% to 6.6 mol% Ca from CaCO3;

[0189] 0.1 mol% to 5.5 mol% Ta from Ta2O5;

[0190] 90.0 mol% to 95.5 mol% Nb from Nb2O5;

[0191] 0.05 mol % to 1.20 mol % Ti from TiO2;

[0192] 0.1 mol% to 6.6 mol% Zr from ZrO2;

[0193] 0.05 mol % to 1.20 mol % Hf from HfO2;

[0194] 0.1 mol% to 2.2 mol% Y from Y2O3;

[0195] A mixture of rare earth oxides, transition metal oxides and glass frits including the following is then added as a dopant along with suitable organic additives to form a ceramic slip:

[0196] 0.1 mol% to 2.4 mol% Mn from MnO2;

[0197] 0.1 mol% to 3.8 mol% Dy from Dy2O3;

[0198] 0.01 mol% to 3.3 mol% of glass frit from CaSiO3.

[0199] Example 7

[0200] Na2CO3, BaCO3, SrCO3, CaCO3, Ta2O5, Nb2O5, ZrO2 and transition metal oxides (such as MnO2) are mixed as starting ceramic raw materials and calcined at 750°C to 1300°C to prepare a precursor, wherein the starting ceramic materials include:

[0201] 90.0 mol % to 95.5 mol % Na from Na2CO3;

[0202] 0.1 mol% to 2.7 mol% Ba from BaCO3;

[0203] 0.1 mol% to 5.3 mol% Sr from SrCO3;

[0204] 0.1 mol% to 6.6 mol% Ca from CaCO3;

[0205] 0.1 mol% to 5.5 mol% Ta from Ta2O5;

[0206] 90.0 mol% to 95.5 mol% Nb from Nb2O5;

[0207] 0.1 mol% to 6.6 mol% Zr from ZrO2;

[0208] 0.1 mol% to 2.2 mol% Mn from MnO2;

[0209] A mixture of rare earth oxides, transition metal oxides and glass frits including the following is then added as a dopant along with suitable organic additives to form a ceramic slip:

[0210] 0.1 mol% to 2.4 mol% Mn from MnO2;

[0211] 0.6 mol% to 5.0 mol% Y from Y2O3;

[0212] 0.01 mol% to 3.30 mol% of glass frit from KF.

[0213] Example 8

[0214] K2CO3, Na2CO3, SrCO3, CaCO3, Ta2O5, Nb2O5, ZrO2, HfO2, transition metal oxide (such as WO3) and glass material (such as SiO2) are mixed as starting ceramic raw materials, and calcined at 750° C. to 1300° C. to prepare a precursor, wherein the starting ceramic materials include:

[0215] 0.1 mol% to 2.0 mol% K from K2CO3;

[0216] 87.0 mol% to 92.5 mol% Na from Na2CO3;

[0217] 0.1 mol% to 5.3 mol% Sr from SrCO3;

[0218] 0.1 mol% to 6.6 mol% Ca from CaCO3;

[0219] 0.1 mol% to 5.5 mol% Ta from Ta2O5;

[0220] 87.0 mol% to 92.5 mol% Nb from Nb2O5;

[0221] 0.1 mol% to 6.6 mol% Zr from ZrO2;

[0222] 0.05 mol % to 1.20 mol % Hf from HfO2;

[0223] 0.01 mol% to 0.80 mol% W from WO3;

[0224] 0.01 mol% to 0.85 mol% Si from SiO2;

[0225] A mixture including rare earth oxides, transition metal oxides and glass frits is then added as a dopant together with suitable organic additives to form a ceramic slip:

[0226] 0.1 mol% to 2.4 mol% Mn from MnO2;

[0227] 0.6 mol% to 4.0 mol% Y from Y2O3;

[0228] 0.01 mol% to 3.30 mol% of glass frit from BaSiO3.

[0229] Example 9

[0230] Na2CO3, BaCO3, SrCO3, CaCO3, Ta2O5, Nb2O5, TiO2, ZrO2, transition metal oxides (such as MoO3), rare earth oxides (such as Y2O3) and glass frits (such as SiO2) are mixed as starting ceramic raw materials, and calcined at 750° C. to 1300° C. to prepare a precursor, wherein the starting ceramic materials include:

[0231] 87.0 mol% to 92.5 mol% Na from Na2CO3;

[0232] 0.1 mol% to 2.7 mol% Ba from BaCO3;

[0233] 0.1 mol% to 5.3 mol% Sr from SrCO3;

[0234] 0.1 mol% to 6.6 mol% Ca from CaCO3;

[0235] 0.1 mol% to 5.5 mol% Ta from Ta2O5;

[0236] 87.0 mol% to 92.5 mol% Nb from Nb2O5;

[0237] 0.05 mol % to 1.20 mol % Ti from TiO2;

[0238] 0.1 mol% to 6.6 mol% Zr from ZrO2;

[0239] 0.01 mol% to 1.80 mol% Mo from MoO3;

[0240] 0.1 mol% to 2.0 mol% Y from Y2O3;

[0241] 0.01 mol% to 1.40 mol% Si from SiO2;

[0242] A mixture including rare earth oxides, transition metal oxides and glass frits is then added as a dopant together with suitable organic additives to form a ceramic slip:

[0243] 0.1 mol% to 2.4 mol% Mn from MnO2;

[0244] 0.6 mol% to 4.0 mol% Y from Y2O3;

[0245] 0.01 mol% to 3.30 mol% of glass frit from CaSiO3.

[0246] Example 10

[0247] Na2CO3, BaCO3, SrCO3, CaCO3, Ta2O5, Nb2O5, TiO2, ZrO2, HfO2 and glass material (such as SiO2) are mixed as starting ceramic raw materials, and calcined at 750° C. to 1300° C. to prepare a precursor, wherein the starting ceramic material includes:

[0248] 90.0 mol % to 95.5 mol % Na from Na2CO3;

[0249] 0.1 mol% to 2.7 mol% Ba from BaCO3;

[0250] 0.1 mol% to 5.3 mol% Sr from SrCO3;

[0251] 0.1 mol% to 6.6 mol% Ca from CaCO3;

[0252] 0.1 mol% to 5.5 mol% Ta from Ta2O5;

[0253] 90.0 mol% to 95.5 mol% Nb from Nb2O5;

[0254] 0.05 mol % to 1.20 mol % Ti from TiO2;

[0255] 0.1 mol% to 6.6 mol% Zr from ZrO2;

[0256] 0.05 mol % to 1.20 mol % Hf from HfO2;

[0257] 0.01 mol% to 1.40 mol% of glass frit from SiO2;

[0258] A mixture of rare earth oxides, transition metal oxides and glass frits including the following is then added as a dopant along with suitable organic additives to form a ceramic slip:

[0259] 0.1 mol% to 2.4 mol% Mn from MnO2;

[0260] 0.01 mol% to 2.60 mol% W from WO3;

[0261] 0.6 mol% to 5.0 mol% Yb from Yb2O3;

[0262] 0.01 mol% to 3.30 mol% of glass frit from B2O3.

[0263] Embodiment 11

[0264] Na2CO3, CaCO3, Nb2O5, Gd2O3 and ZrO2 are mixed as starting ceramic raw materials and calcined at 750°C to 1300°C to prepare a precursor, wherein the starting ceramic materials include:

[0265] 84.0 mol% to 95.2 mol% Na from Na2CO3;

[0266] 0.1 mol % to 15.3 mol % Ca from CaCO3;

[0267] 84.0 mol% to 95.2 mol% Nb from Nb2O5;

[0268] 0.1 mol% to 15.3 mol% Zr from ZrO2;

[0269] 0.1 mol% to 7.2 mol% Gd from Gd2O3;

[0270] A mixture of transition metal oxides and glass frits including the following is then added as a dopant to the main components:

[0271] 0.1 mol% to 3.8 mol% Mn from MnCO3;

[0272] 0.01 mol% to 4.2 mol% of glass frit from SiO2.

[0273] Example 12

[0274] Na2CO3, CaCO3, Nb2O5, Gd2O3, Ta2O5 and ZrO2 are mixed as starting ceramic raw materials and calcined at 750°C to 1300°C to prepare a precursor, wherein the starting ceramic material includes: 84.0 mol% to 95.2 mol% of Na from Na2CO3;

[0275] 0.1 mol % to 15.3 mol % Ca from CaCO3;

[0276] 61.0 mol% to 75.6 mol% Nb from Nb2O5;

[0277] 0.5 mol% to 23.4 mol% Ta from Ta2O5;

[0278] 0.1 mol% to 15.1 mol% Zr from ZrO2;

[0279] 0.1 mol% to 6.6 mol% Gd from Gd2O3;

[0280] A mixture of transition metal oxides and glass frits including the following is then added as a dopant to the main components:

[0281] 0.1 mol% to 2.9 mol% Mn from MnCO3;

[0282] 0.1 mol% to 3.3 mol% of glass frit from SiO2.

[0283] Preparation of ceramic disc samples

[0284] The main components and the auxiliary components of the ceramic powder are weighed in the proportions listed in the embodiment and wet mixed with a ball mill for 12 to 30 hours. Then, the mixture is dried at 150°C for 1 to 8 hours. The binder solution is added to the mixture in the mortar and then granulated to form particles. Then, the obtained particles are filled into a steel mold with a diameter of 13 mm and press-molded at a pressure of 200 MPa to produce a disc compact. The obtained compact is fired in air at a maximum temperature of 375°C for 10 to 100 hours to burn out the organic binder. Next, firing is performed in a reducing atmosphere to obtain a sintered disc. Firing is performed at a peak temperature of 750°C to 1300°C, and the holding time is 1 to 6 hours. Then, silver electrodes are applied to both surfaces of the sintered body to obtain disc ceramic capacitors corresponding to Examples 11 and 12.

[0285] Preparation of MLCC samples

[0286] By sintering in the temperature range of 750°C to 1300°C, a sintered MLCC sheet with a standard size of 3.2 mm×1.6 mm and nickel internal electrodes was obtained. The sintered MLCC sheet contained 19 active dielectric ceramic layers and 20 nickel electrodes. The average thickness of the dielectric ceramic layer was determined to be about 12 μm.

[0287] Electrical Measurements

[0288] The electrostatic capacitance and dielectric loss were measured for each composition at a temperature range of -55°C to 200°C, at 1 kHz and AC 1 V. The temperature coefficient of capacitance (TCC) was calculated according to the following equation:

[0289] TCC(%)=[(C T -C 25 ) / C 25 ]×100

[0290] Where T is the temperature at which the measurement is made, C T and C 25 They are the electrostatic capacitance at temperature T and 25°C respectively.

[0291] The breakdown voltage (BDV) was measured at 25°C with a voltage ramp rate of 5 V per second.

[0292] The insulation resistance (IR) was measured after charging at 50 V DC for 60 seconds at 25°C.

[0293] Table 3 provides the dielectric properties of the disks prepared in Example 11 and Example 12 fired at 1250°C.

[0294] Table 3

[0295] Dielectric constant at 25°C TCC in the range of -55°C to 200°C Embodiment 11 985 -0.98% to 4.67% Example 12 101 -22.4% to 13.11%

[0296] The results given in Table 3 show that a wide range of dielectric constants can be obtained with a temperature coefficient of capacitance (TCC) within ±20% of the capacitance at 25°C, and more preferably within ±5% of the capacitance at 25°C.

[0297] Table 4 provides the dielectric properties of the MLCCs prepared by Example 11 and Example 12 fired at 1250°C.

[0298] Table 4

[0299] TCC in the range of -55°C to 200°C -18.54% to 12.4% Dielectric loss at 25°C 0.8% Insulation resistance at 25°C 69.93GΩ Breakdown voltage at 25°C 1143V

[0300] The results in Table 4 demonstrate the advantages of using the ceramics of the present invention in multilayer ceramic capacitors.

[0301] The slurry is coated on a carrier film using a doctor blade method and further formed into a ceramic green sheet using a tape casting process. After a suitable drying process, a conductive ink mainly containing a base metal (such as Ni, Cu or an alloy thereof) is used to form a ceramic green sheet. Figure 1 The internal electrodes 3a and 3b are screen-printed onto the ceramic green sheet. Preferably, nickel or an alloy mainly composed of nickel is used.

[0302] The obtained product is further processed into green sheets by a stacking process. A plurality of ceramic green sheets without printed electrodes are stacked as a bottom covering layer 4b; then a plurality of ceramic green sheets with printed electrodes are laminated in alternating directions to form alternating electrodes 3a and 3b terminated at opposite ends; finally, a certain number of ceramic green sheets without printed electrodes are stacked as a top covering layer 4a. The laminate is then pressed at 20°C and 120°C to improve the adhesion of all stacked layers, and further cut into individual green sheets. There is no particular limitation on the number of layers herein, and ten to hundreds of layers are suitable for illustrating the present invention.

[0303] The green sheet is heated at 200°C to 700°C for 0.1 to 100 hours in air or a slightly reducing atmosphere to burn off the binder, and then heated at 750°C to 1300°C in an atmosphere of 10 -16 atm to 10 -4 Atm reducing atmosphere. After sintering, -14 atm to 10 -3 The sheet may be further subjected to a reoxidation step by heating to a temperature not exceeding 1100° C. under an oxygen partial pressure of 100 atm. Thus, a sintered sheet is obtained.

[0304] The sintered sheet is rounded by barrel or sandblasting to expose the internal electrodes formed at both ends of the ceramic sintered body. Then, external electrodes 5a and 5b are formed at both ends in the following manner: (1) Copper terminals are formed by applying a suitable copper paste to both ends of the sintered sheet, followed by baking at 600°C to 1000°C in nitrogen or a slightly reducing atmosphere for 1 minute to 60 minutes; (2) a nickel plating layer and a tin plating layer or other suitable solder component are electroplated on the copper terminals by a drum roller plating method to enhance solderability and prevent oxidation of the copper external electrodes. Thus, a multilayer ceramic capacitor 1 formed of base metal electrodes 3a and 3b and a dielectric ceramic layer 2 including the dielectric composition of the present invention is obtained.

[0305] The present invention discloses a dielectric ceramic composition that can be used in high temperature applications. This ceramic formulation can be co-fired with a base metal electrode in a reducing atmosphere. Therefore, a multilayer ceramic capacitor can be produced using the disclosed dielectric ceramic composition and a base metal internal electrode (such as Ni).

[0306] Throughout the specification, the ranges listed include all intermediate values ​​with the same number of significant figures. As a non-limiting example, a range listed of 0.01 to 0.05 includes: 0.01, 0.02, 0.03, 0.04, and 0.05. If a listed range has two values ​​with different significant figures, the value with the smallest incremental significant figure determines the significant figures of both. As a non-limiting example, if a range is listed as 1.0 to 5, it means all values ​​from 1.0 to 5.0.

[0307] The following are incorporated herein by reference:

[0308] U.S. Patent No. 9,564,271, Banno et al.;

[0309] WO 2018-062084 A1, Banno;

[0310] U.S. Patent No. 10,710,934 to Banno et al.

[0311] Lead-free antiferroelectric:xCaZrO3-(1-x)NaNbO3 system (0≤x≤0.10), Shimizu et al., Dalton Transactions, Vol. 44, pp. 10763-10772, 2015;

[0312] Strategy for stabilization of the antiferroelectric phase(Pbma)over the metastable ferroelectric phase(P21ma) to establish double loop hysteresisin lead-free(1-x)NaNbO3-xSrZrO3 solid solution, Guo et al., Journal of Applied Physics, Volume 117, Page 214103, 2015;

[0313] A perovskite lead-free antiferroelectric xCaHfO3-(1-x)NaNbO3 with induced double hysteresis loops at room temperature, Gao et al., Journal of Applied Physics, Vol. 120, pp. 204102, 2016;

[0314] Advantages of low partial pressure of oxygen processing of alkaliniobate: NaNbO3, Shimizu et al., Journal of the American Ceramic Society, Vol. 97, No. 6, pp. 1791-1796, 2014; and

[0315] Base metal co-fired multilayer piezoelectrics, Gao et al., Actuators, Vol. 5, No. 1, p. 8, 2016.

[0316] The present invention will be described with reference to the accompanying drawings, which are an integral part of the description provided to make the present invention clear, but are not limiting. In the various figures, similar elements will be numbered according to the figures. The present invention has been described with reference to preferred embodiments, but is not limited thereto. Those skilled in the art will realize the additional embodiments described and set forth in the appended claims.

Claims

1. A dielectric ceramic composition comprising: The main components are defined as: <h2 style=";text-align:left;direction:ltr">[(Na<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> K<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> s <h2 style=";text-align:left;direction:ltr"> A<h2 style=";text-align:left;direction:ltr"> 1-s <h2 style=";text-align:left;direction:ltr"> ]<h2 style=";text-align:left;direction:ltr"> m <h2 style=";text-align:left;direction:ltr"> [(Nb<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> u <h2 style=";text-align:left;direction:ltr"> B1<h2 style=";text-align:left;direction:ltr"> v <h2 style=";text-align:left;direction:ltr"> B2<h2 style=";text-align:left;direction:ltr"> w <h2 style=";text-align:left;direction:ltr"> )]O3 in: A is at least one element selected from the alkaline earth element group of Mg, Ca, Sr and Ba; B1 is at least one element selected from Ti, Zr, Hf and Sn; B2 is at least one element selected from the transition metal element group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; And among them: x, y, s, u, v and w are the mole fractions of each element, and m is [(Na 1-x K x ) s A 1-s ] and [(Nb 1-y Ta y ) u B1 v B2 w )] molar ratio; in 0.93≤m≤1.07; 0.7≤s≤1.0; 0≤x≤0.05; 0≤y≤0.65; 0.7≤u≤1.0; 0≤v≤0.3; 0.001≤w≤0.100; A first subcomponent comprising at least one rare earth selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu; and A second component includes glass frit; and The dielectric ceramic composition has a capacitance temperature coefficient of ±25 at a temperature of -55°C to 200°C.

2. The dielectric ceramic composition according to claim 1, wherein the first subcomponent is not more than 10 mol% based on the main component.

3. The dielectric ceramic composition according to claim 1, wherein the second subcomponent is selected from the group consisting of fluorides, silicates, borides and oxides. 4 . The dielectric ceramic composition according to claim 1 , wherein the second subcomponent is in a range of 0.01 mol % to 15.00 mol % with respect to the main component. The dielectric ceramic composition according to claim 1 , wherein the second subcomponent does not contain Li.

6. A dielectric ceramic composition comprising: The main components are defined as: <h2 style=";text-align:left;direction:ltr">[(Na<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> K<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> s <h2 style=";text-align:left;direction:ltr"> A<h2 style=";text-align:left;direction:ltr"> 1-s <h2 style=";text-align:left;direction:ltr"> ]<h2 style=";text-align:left;direction:ltr"> m <h2 style=";text-align:left;direction:ltr"> [(Nb<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> u <h2 style=";text-align:left;direction:ltr"> B1<h2 style=";text-align:left;direction:ltr"> v <h2 style=";text-align:left;direction:ltr"> B2<h2 style=";text-align:left;direction:ltr"> w <h2 style=";text-align:left;direction:ltr"> )]O3 in: A is at least one element selected from the alkaline earth element group of Mg, Ca, Sr and Ba; B1 is at least one element selected from Ti, Zr, Hf and Sn; B2 is at least one element selected from the transition metal element group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; And among them: x, y, s, u, v and w are the mole fractions of each element, and m is [(Na 1-x K x ) s A 1-s ] and [(Nb 1-y Ta y ) u B1 v B2 w )] molar ratio; in 0.93≤m≤1.07; 0.7≤s≤1.0; 0≤x≤0.05; 0≤y≤0.65; 0.7≤u≤1.0; 0≤v≤0.3; 0.001≤w≤0.100; A first subcomponent comprising at least one rare earth selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu; and A second component includes glass frit; and The dielectric ceramic composition has a dielectric constant of at least 100 at 25°C.

7. The dielectric ceramic composition according to claim 6, wherein the dielectric ceramic composition has a dielectric constant of at least 900 at 25°C.

8. A multilayer ceramic capacitor comprising: A plurality of dielectric ceramic layers, wherein each of said layers comprises a dielectric composition defined by: The main components are defined as: <h2 style=";text-align:left;direction:ltr">[(Na<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> K<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> s <h2 style=";text-align:left;direction:ltr"> A<h2 style=";text-align:left;direction:ltr"> 1-s <h2 style=";text-align:left;direction:ltr"> ]<h2 style=";text-align:left;direction:ltr"> m <h2 style=";text-align:left;direction:ltr"> [(Nb<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> u <h2 style=";text-align:left;direction:ltr"> B1<h2 style=";text-align:left;direction:ltr"> v <h2 style=";text-align:left;direction:ltr"> B2<h2 style=";text-align:left;direction:ltr"> w <h2 style=";text-align:left;direction:ltr"> )]O3 in: A is at least one element selected from the alkaline earth element group of Mg, Ca, Sr and Ba; B1 is at least one element selected from Ti, Zr, Hf and Sn; B2 is at least one element selected from the transition metal element group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; And among them: x, y, s, u, v and w are the mole fractions of each element, and m is [(Na 1-x K x ) s A 1-s ] and [(Nb 1-y Ta y ) u B1 v B2 w )] molar ratio; in 0.93≤m≤1.07; 0.7≤s≤1.0; 0≤x≤0.05; 0≤y≤0.65; 0.7≤u≤1.0; 0≤v≤0.3; 0.001≤w≤0.100; A first subcomponent comprising at least one rare earth selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu; and The second auxiliary component includes glass material; wherein the dielectric composition has a capacitance temperature coefficient of ±25 at a temperature of -55°C to 200°C; a plurality of internal electrodes comprising base metals Ni, Cu or alloys thereof; and A pair of external electrodes is formed at each end of the capacitor element body.

9. The multilayer ceramic capacitor according to claim 8, wherein the first subcomponent is not more than 10 mol% with respect to the main component.

10. The multilayer ceramic capacitor of claim 8, wherein the second subcomponent is selected from the group consisting of fluorides, silicates, borides, and oxides.

11. The multilayer ceramic capacitor of claim 8, wherein the second subcomponent is in a range of 0.01 mol% to 15.00 mol% with respect to the main component. 12 . The multilayer ceramic capacitor according to claim 8 , wherein the second subcomponent does not contain Li.

13. A multilayer ceramic capacitor comprising: A plurality of dielectric ceramic layers, wherein each of said layers comprises a dielectric composition defined by: The main components are defined as: <h2 style=";text-align:left;direction:ltr">[(Na<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> K<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> s <h2 style=";text-align:left;direction:ltr"> A<h2 style=";text-align:left;direction:ltr"> 1-s <h2 style=";text-align:left;direction:ltr"> ]<h2 style=";text-align:left;direction:ltr"> m <h2 style=";text-align:left;direction:ltr"> [(Nb<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> u <h2 style=";text-align:left;direction:ltr"> B1<h2 style=";text-align:left;direction:ltr"> v <h2 style=";text-align:left;direction:ltr"> B2<h2 style=";text-align:left;direction:ltr"> w <h2 style=";text-align:left;direction:ltr"> )]O3 in: A is at least one element selected from the alkaline earth element group of Mg, Ca, Sr and Ba; B1 is at least one element selected from Ti, Zr, Hf and Sn; B2 is at least one element selected from the transition metal element group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; And among them: x, y, s, u, v and w are the mole fractions of each element, and m is [(Na 1-x K x ) s A 1-s ] and [(Nb 1-y Ta y ) u B1 v B2 w )] molar ratio; in 0.93≤m≤1.07; 0.7≤s≤1.0; 0≤x≤0.05; 0≤y≤0.65; 0.7≤u≤1.0; 0≤v≤0.3; 0.001≤w≤0.100; A first subcomponent comprising at least one rare earth selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu; and The second auxiliary component includes glass material; wherein the dielectric composition has a dielectric constant of at least 100 at 25°C; a plurality of internal electrodes comprising base metals Ni, Cu or alloys thereof; and A pair of external electrodes is formed at each end of the capacitor element body.

14. The multilayer ceramic capacitor of claim 13, wherein the dielectric composition has a dielectric constant of at least 900 at 25°C.

15. A method of forming a multilayer ceramic capacitor, comprising: forming a dielectric ceramic precursor; interleaving layers of the dielectric ceramic precursor with metal layers to form a stack; Compressing the stack and sintering the material obtained after compressing the stack to form a dielectric ceramic layer, the dielectric ceramic layer having a dielectric composition defined by: The main components are defined as: <h2 style=";text-align:left;direction:ltr">[(Na<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> K<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> s <h2 style=";text-align:left;direction:ltr"> A<h2 style=";text-align:left;direction:ltr"> 1-s <h2 style=";text-align:left;direction:ltr"> ]<h2 style=";text-align:left;direction:ltr"> m <h2 style=";text-align:left;direction:ltr"> [(Nb<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> u <h2 style=";text-align:left;direction:ltr"> B1<h2 style=";text-align:left;direction:ltr"> v <h2 style=";text-align:left;direction:ltr"> B2<h2 style=";text-align:left;direction:ltr"> w <h2 style=";text-align:left;direction:ltr"> )]O3 in: A is at least one element selected from the alkaline earth element group of Mg, Ca, Sr and Ba; B1 is at least one element selected from Ti, Zr, Hf and Sn; B2 is at least one element selected from the transition metal element group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; And among them: x, y, s, u, v and w are the mole fractions of each element, and m is [(Na 1-x K x ) s A 1-s ] and [(Nb 1-y Ta y ) u B1 v B2 w )] molar ratio; in 0.93≤m≤1.07; 0.7≤s≤1.0; 0≤x≤0.05; 0≤y≤0.65; 0.7≤u≤1.0; 0≤v≤0.3; 0.001≤w≤0.100; A first subcomponent comprising at least one rare earth selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu; and The second auxiliary component includes glass material; The ceramic composition has a capacitance temperature coefficient of ±25 at a temperature of -55°C to 200°C.

16. The method of forming a multilayer ceramic capacitor of claim 15, wherein the layer of dielectric ceramic precursor is prepared as a ceramic green body slurry comprising a mixture of inorganic materials and organic additives, wherein the inorganic materials include at least one combination of a precursor and a dopant.

17. The method of forming a multilayer ceramic capacitor according to claim 16, wherein the dopant is at least one selected from the group consisting of: A transition metal element selected from V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; A rare earth element selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu; and A glass frit selected from the group consisting of fluorides, silicates, borides and oxides.

18. The method of forming a multilayer ceramic capacitor of claim 16, comprising sintering the ceramic green body slurry.

19. The method of forming a multilayer ceramic capacitor according to claim 15, wherein the sintering is performed at a temperature of 750°C to 1300°C.

20. The method for forming a multilayer ceramic capacitor according to claim 15, wherein the sintering is performed at an oxygen partial pressure of 10 -16 atm to 10 -4 atm atmosphere.

21. The method of forming a multilayer ceramic capacitor according to claim 15, wherein the first subcomponent does not exceed 10 mol% with respect to the main component.

22. The method of forming a multilayer ceramic capacitor according to claim 15, wherein the second subcomponent is selected from the group consisting of fluorides, silicates, borides, and oxides.

23. The method of forming a multilayer ceramic capacitor according to claim 15, wherein the second subcomponent is in a range of 0.01 mol% to 15.00 mol% with respect to the main component.

24. The method of forming a multilayer ceramic capacitor according to claim 15, wherein the second subcomponent does not contain Li.

25. The method of forming a multilayer ceramic capacitor of claim 15, wherein the metal layer comprises a base metal of Ni, Cu, or an alloy thereof.

26. The method of forming a multilayer ceramic capacitor of claim 15, further comprising forming a pair of external electrodes at each end of the capacitor element.

27. A method of forming a multilayer ceramic capacitor, comprising: forming a dielectric ceramic precursor; interleaving layers of the dielectric ceramic precursor with metal layers to form a stack; Compressing the stack and sintering the material obtained after compressing the stack to form a dielectric ceramic layer, the dielectric ceramic layer having a dielectric composition defined by: The main components are defined as: <h2 style=";text-align:left;direction:ltr">[(Na<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> K<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> s <h2 style=";text-align:left;direction:ltr"> A<h2 style=";text-align:left;direction:ltr"> 1-s <h2 style=";text-align:left;direction:ltr"> ]<h2 style=";text-align:left;direction:ltr"> m <h2 style=";text-align:left;direction:ltr"> [(Nb<h2 style=";text-align:left;direction:ltr"> 1-y <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> u <h2 style=";text-align:left;direction:ltr"> B1<h2 style=";text-align:left;direction:ltr"> v <h2 style=";text-align:left;direction:ltr"> B2<h2 style=";text-align:left;direction:ltr"> w <h2 style=";text-align:left;direction:ltr"> )]O3 in: A is at least one element selected from the alkaline earth element group of Mg, Ca, Sr and Ba; B1 is at least one element selected from Ti, Zr, Hf and Sn; B2 is at least one element selected from the transition metal element group consisting of V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu and Zn; And among them: x, y, s, u, v and w are the mole fractions of each element, and m is [(Na 1-x K x ) s A 1-s ] and [(Nb 1-y Ta y ) u B1 v B2 w )] molar ratio; in 0.93≤m≤1.07; 0.7≤s≤1.0; 0≤x≤0.05; 0≤y≤0.65; 0.7≤u≤1.0; 0≤v≤0.3; 0.001≤w≤0.100; A first subcomponent comprising at least one rare earth selected from the group consisting of Y, Sc, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Yu; and The second auxiliary component includes glass material; The ceramic composition has a dielectric constant of at least 100 at 25°C.

28. The method of forming a multilayer ceramic capacitor of claim 27 wherein the ceramic composition has a dielectric constant of at least 900 at 25°C.

Citation Information

Patent Citations

  • Tool handle

    CA110264A

  • Dielectric ceramic composition and ceramic capacitor

    US10710934B2

  • Dielectric ceramic composition, stacked ceramic capacitor using the same, and method of manufacturing the same

    US9564271B2

  • Dielectric ceramic composition, and ceramic capacitor

    WO2018062084A1

  • Dielectric ceramics and multi-layer ceramic capacitor

    CN101081734A